2014
DOI: 10.1002/jcp.24610
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 and FGF2 Stimulate the Epithelial-Mesenchymal Transition of HERS Cells Through a MEK-Dependent Mechanism

Abstract: Hertwig's epithelial root sheath (HERS) cells participate in cementum formation through epithelial-mesenchymal transition (EMT). Previous studies have shown that transforming growth factor beta 1 (TGF-β1) and fibroblast growth factor 2 (FGF2) are involved in inducing EMT. However, their involvement in HERS cell transition remains elusive. In this study, we confirmed that HERS cells underwent EMT during the formation of acellular cementum. We found that both TGF-β1 and FGF2 stimulated the EMT of HERS cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 40 publications
4
68
0
Order By: Relevance
“…Support of our findings is derived from other reports that FGF2 in concert with IL-1b promotes EMT in corneal endothelial cells, 9 whereas FGF2 alone is capable of inducing EMT in Hertwig epithelial root sheath cells during cementum formation in tooth development. 29 Another report found that MCF-7 cells undergoing EMT up-regulate TFPI2 gene expression in excess of 300-fold, 30 which corroborates our findings. TFPI2 inhibits fibrinolysis, an important function of the mesothelium that prevents adhesion of organs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Support of our findings is derived from other reports that FGF2 in concert with IL-1b promotes EMT in corneal endothelial cells, 9 whereas FGF2 alone is capable of inducing EMT in Hertwig epithelial root sheath cells during cementum formation in tooth development. 29 Another report found that MCF-7 cells undergoing EMT up-regulate TFPI2 gene expression in excess of 300-fold, 30 which corroborates our findings. TFPI2 inhibits fibrinolysis, an important function of the mesothelium that prevents adhesion of organs.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike the other cytokines, FGF2, which is secreted in a nonclassic secretion pathway dependent on caspase-1, was up-regulated in response to asbestos after pretreatment with IL-1Ra. Because FGF2 can initiate EMT in corneal endothelial cells and Hertwig epithelial root sheath cells cells, 9,29 it may explain why the mesothelial cells eventually undergo MFT after the delay imposed by the antagonist. It is a possibility that FGF2 and IL-1b play pivotal roles in asbestos-induced MFT.…”
Section: Inflammasomes In Mftmentioning
confidence: 99%
“…Previous studies have shown that Erk is rapidly activated by TGF-β in cell culture models of EMT. Furthermore, specific inhibition of MEK inhibits cells from adopting key morphological features associated with EMT [38]. Raf activation confers protection against TGF-β-induced apoptosis by enhancing the proinvasive effects of TGF-β [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging concepts suggest that repeated injury to bronchiole-like epithelial cells and hyperplastic type II alveolar epithelial cells induces honeycomb fibrosis (Katzenstein and Myers, 1998; King et al, 2011), and stem cells also play a key role in the development of PF (Chilosi et al, 2010; Mora and Rojas, 2013; Toonkel et al, 2013). Damaged epithelial cells produce various pro-fibrotic factors, including transforming growth factor β (TGF-β) (Pittet et al, 2001; Polosukhin et al, 2012) and fibroblast growth factor (FGF)-2 (Xiao et al, 2012), resulting in epithelial-to-mesenchymal transition (EMT) contributing to PF (Chen et al, 2014; Kim et al, 2006; Willis et al, 2005; Zhou et al, 2012a). …”
Section: Introductionmentioning
confidence: 99%